Long-service-life large precast block for dry quenching furnace and preparation method of long-service-life large precast block
By using prefabricated blocks with chimeric structures, combined with specific materials and processes, the problems of short service life and insufficient flexural resistance of existing dry quenching oven prefabricated blocks are solved, and higher heat resistance and service life are achieved.
Patent Information
- Application Number
- CN202411865758.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The prefabricated blocks of existing dry coke quenching ovens have short service life in high temperature and oxidation atmospheres, and lack of flexural resistance and thermal shock stability.
The first block made of materials such as Al2O3, SiC, mullite and aluminum silicate modified fibers, and a second block made of materials such as kaolin, silicate cement, diatomaceous earth and heat-resistant steel fibers are formed through wet grinding, molding and sintering processes.
The heat resistance, oxidation resistance and thermal shock resistance of the prefabricated blocks are significantly improved, the service life is extended, and the absorption capacity of thermal energy and pressure at high temperatures is optimized.
Smart Images

Figure CN119899037A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of prefabricated blocks for dry quenching coke ovens, and in particular to a long-life large-scale prefabricated block for dry quenching coke ovens and a preparation method thereof. Background Art
[0002] The dry quenching coke oven is a coking process equipment used to process the red coke produced during the coking process. The basic principle of dry quenching coke is to use gas to exchange heat with the red-hot red coke in the dry quenching oven, thereby cooling the red coke. In this process, the red coke is loaded from the top of the dry quenching oven, and the low-temperature inert gas is blown into the red coke layer in the cooling section of the dry quenching oven by the circulating fan. After absorbing the heat of the red coke, the inert gas with increased temperature is discharged from the annular flue of the dry quenching oven, and then enters the dry quenching coke waste heat boiler for heat exchange, generating steam for power generation or as a steam heat source for steel plants. The cooled inert gas is blown into the dry quenching oven again by the circulating fan to achieve a closed cycle.
[0003] The prefabricated blocks of the CDQ oven are usually made of high-grade refractory materials through molding, drying and calcining processes to withstand high temperatures and wear. According to existing technical information, the use of refractory materials used in CDQ ovens also has some disadvantages. For example, some materials (such as mullite bricks) are easily oxidized at high temperatures and are not suitable for use in oxidizing atmospheres. In addition, some refractory materials currently used, such as mullite-silicon carbide bricks, may not have stable anti-bending properties and thermal shock stability, resulting in their service life needs to be improved. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a long-life large-scale prefabricated block for a dry quenching coke oven and a preparation method thereof.
[0005] A long-life large prefabricated block for a dry quenching coke oven, the prefabricated block comprising a first block and a second block which are spliced to each other, the first block facing the inside of the coke oven, and the second block facing the outside of the coke oven; the mass ratio of the first block to the second block is 1:1-1.5, the first block is provided with a convex block, and the second block is provided with a groove matching the convex block;
[0006] The raw materials of the first block include, by weight: 25 to 40 parts of Al 2 O 3 , 18 to 25 parts of SiC, 10 to 15 parts of mullite, and 5 to 7 parts of aluminum silicate modified fiber; the raw materials of the second block include: 20 to 30 parts of kaolin, 10 to 15 parts of silicate cement, 10 to 15 parts of diatomaceous earth, and 3 to 5 parts of heat-resistant steel fiber.
[0007] Note: Through the differentiated settings of the above-mentioned first block and the second block, different settings can be made according to different requirements inside and outside the furnace. In addition to heat resistance, the raw materials facing the furnace also need to enhance their stability and corrosion resistance. For example, alumina and mullite have good refractoriness and corrosion resistance, and aluminum silicate modified fibers can improve the material's oxidation resistance, thermal shock resistance and thermal insulation performance; while the raw materials facing outside the furnace require certain thermal insulation performance and mechanical strength. For example, silicate cement can improve the mechanical strength of the prefabricated block, and diatomaceous earth can improve the thermal insulation effect. The combination of the above-mentioned raw materials and the interlocking of the first block and the second block can be beneficial to the absorption of heat energy and pressure, and compared with bricks of a single material, its service life can be significantly improved.
[0008] The present invention provides a method for preparing a long-life large-scale prefabricated block for a dry quenching coke oven, comprising the following steps:
[0009] S1, mixing the raw materials of the first block, adding yttrium oxide accounting for 0.5-1wt% of the total weight of the raw materials of the first block, then putting them into a ball mill, adding water accounting for 20-25wt% of the total weight of the raw materials of the first block, and wet grinding for 2-4h. After wet grinding, drying at 100-150° C. for 1-2h, granulating at a granulating pressure of 5-10MPa, and then molding at a molding pressure of 20-30MPa to obtain a first molded block;
[0010] S2, mixing half of the mass of kaolin, half of the mass of diatomaceous earth and one third of the mass of heat-resistant steel fiber in the second block raw material to form a first mixture, placing the first mixture in a ball mill, adding 10-13wt% of water accounting for the total weight of the raw materials of the second block, wet grinding for 1-2h, then freeze-drying for 10-15min, and then heating to 160-170°C for granulation at a granulation pressure of 8-10MPa to obtain first particles;
[0011] S3, mixing the remaining half of the mass of kaolin, the remaining half of the mass of diatomaceous earth, and the remaining two-thirds of the mass of heat-resistant steel fiber and silicate cement in the raw materials of the second block to form a second mixture, then putting the second mixture into a ball mill, adding water accounting for 10-13wt% of the total weight of the raw materials of the second block, wet grinding for 1-2h, and then drying at 90-100°C for 1-2h, and then granulating at a granulation pressure of 4-6MPa to obtain second particles; laying the first particles on the lower layer and laying the second particles on the upper layer of the first particles, and then molding at a molding pressure of 25-35MPa to obtain a second molded block, wherein the groove is located on the second particle laying layer;
[0012] S4, placing the second molding block into a high temperature furnace for sintering at a sintering temperature of 1600-1800° C., after sintering for 1-2 hours, splicing the first molding block with the second molding block, and then continuing to sinter for 2-3 hours to obtain a prefabricated block.
[0013] Description: Through the above-mentioned preparation method, the brick performance of the first block and the second block can be better. By adding the auxiliary agent yttrium oxide to the first raw material, the refractoriness and thermal stability can be further enhanced, so that the performance can be maintained at extreme temperatures, which helps to increase the service life of the furnace body. By setting parameters such as wet grinding and molding, a preferred preparation method can be provided to obtain a first block with better performance. By distinguishing the raw materials in the second block, the different absorption properties and mechanical properties of the first mixture and the second mixture can be utilized, thereby reducing the fatigue loss of the material at high temperature and optimizing the service life of the prefabricated block.
[0014] Furthermore, the wet-milled Al 2 O 3 The particle size of SiC and mullite is 150-200 meshes, the aspect ratio of the aluminum silicate modified fiber is 10-15, and the fiber diameter of the aluminum silicate modified fiber is 10-20 μm.
[0015] Note: Through the above-mentioned comparison of particle sizes, the first block can be fired to have better performance, and has better heat resistance and oxidation resistance. Exceeding this range may change the strength and other properties of the bricks, and thus its performance and life may be reduced.
[0016] Furthermore, in S2 and S3, the particle size of the wet-ground kaolin, silicate cement and diatomaceous earth is 100-200 mesh, and the diameter of the heat-resistant steel fiber is 2-10 μm and the length is 3-6 mm.
[0017] Note: The above-mentioned particle size setting can optimize the material properties of the second block. Exceeding this range may cause changes in the mechanical strength of the brick, making it unsuitable for long-term use.
[0018] Furthermore, in S2, the freeze-drying temperature is -40 to -20°C.
[0019] Furthermore, the angle between the side surface of the protrusion and the upper surface of the first block is 20-45°.
[0020] Note: The above angle setting is more preferred. Due to the impact of thermal radiation generated by heat and gas pressure, the combination effect of this angle is better. If a right-angle connection is directly adopted, the contact surface between the first block and the second block is reduced, which may cause poor absorption of pressure and thermal radiation, thereby affecting the service life of the prefabricated block.
[0021] Furthermore, the aluminum silicate modified fiber is obtained by nano-enhancing and modifying the aluminum silicate fiber with nano-aluminum titanate.
[0022] Description: Aluminum titanate has a unique crystal structure and excellent thermal stability, and can maintain stable performance at high temperatures. Combining aluminum titanate particles with aluminum silicate fibers can enhance the thermal stability and mechanical properties of the fibers and broaden their application range.
[0023] Furthermore, the preparation method of the aluminum silicate modified fiber comprises:
[0024] S1-1, adding nano-aluminum titanate into acetone solvent, and dispersing by ultrasonication to form a first mixed solution with a mass fraction of nano-aluminum titanate of 15-20%;
[0025] S1-2, mixing the first mixed solution with aluminum silicate fiber at a ratio of 10 ml: 2-5 g at 40-80° C. to obtain a second mixed solution;
[0026] S1-3. Then, the second mixed liquid is subjected to a heating evaporation treatment. The heating evaporation treatment is as follows: standing at 120-150°C until the liquid in the second mixed liquid is completely evaporated, and then standing at 160-200°C for 1-2 hours to obtain aluminum silicate modified fibers.
[0027] Description: Through the above preparation method, nano-aluminum titanate particles can be compounded onto aluminum silicate fibers to improve the various properties of aluminum silicate fibers. The thermal insulation properties of aluminum silicate fibers can be improved through nano-enhancement modification. The aluminum silicate fibers after nano-enhancement modification have more stable performance in harsh environments such as high temperature and high pressure.
[0028] Furthermore, the ultrasonic frequency of the ultrasonic dispersion is 60-70 kHz, the ultrasonic time is 5-8 min, the stirring speed of the mixed stirring is 200-500 rpm, and the stirring time is 20-30 min.
[0029] Note: The above parameters are applicable to the preparation process of aluminum silicate modified fibers. If the parameters are beyond this range, the composite effect of nano-aluminum titanate and aluminum silicate fibers may be poor, thus affecting the performance of aluminum silicate modified fibers.
[0030] The beneficial effects of the present invention are:
[0031] The present invention distinguishes between the first block and the second block, and can make different settings according to different requirements inside and outside the furnace. The raw materials facing the furnace have enhanced stability and corrosion resistance in addition to heat resistance; while the raw materials facing outside the furnace require certain thermal insulation performance and mechanical strength. The combination of their respective raw materials and the interlocking structure of the first block and the second block can be beneficial to the absorption of heat energy and pressure, and compared with bricks of a single material, their service life can be increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a longitudinal sectional schematic diagram of a prefabricated block according to an embodiment of the present invention;
[0033] In the figure, 1-first block, 2-second block. DETAILED DESCRIPTION
[0034] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0035] Embodiment 1: A long-life large prefabricated block for a dry quenching coke oven, the prefabricated block comprising a first block and a second block spliced to each other, the first block facing the inside of the coke oven, and the second block facing the outside of the coke oven; the mass ratio of the first block to the second block is 1:1.2, the first block is provided with a convex block, and the second block is provided with a groove matching the convex block;
[0036] The raw materials of the first block include, by weight: 30 parts of Al 2 O 3 , 20 parts of SiC, 12 parts of mullite, and 6 parts of aluminum silicate modified fiber; the raw materials of the second block include: 25 parts of kaolin, 13 parts of silicate cement, 13 parts of diatomaceous earth, and 4 parts of heat-resistant steel fiber.
[0037] The side surface of the protrusion is at 40° to the plane where the first block is located;
[0038] The aluminum silicate modified fiber is obtained by subjecting the aluminum silicate fiber to nano-enhancement modification with nano-aluminum titanate.
[0039] The preparation method of the aluminum silicate modified fiber comprises:
[0040] S1-1, adding nano-aluminum titanate to an acetone solvent, and dispersing by ultrasound, wherein the ultrasonic frequency of the ultrasonic dispersion is 65 kHz and the ultrasonic time is 7 minutes, to form a first mixed solution with a mass fraction of nano-aluminum titanate of 17%;
[0041] S1-2, mixing the first mixed solution with aluminum silicate fiber at a ratio of 10 ml:4 g at 60° C., with a stirring speed of 300 rpm and a stirring time of 25 min to obtain a second mixed solution;
[0042] S1-3. Then, the second mixed liquid is subjected to a heating evaporation treatment. The heating evaporation treatment is as follows: standing at 140° C. until the liquid in the second mixed liquid is completely evaporated, and then standing at 170° C. for 1.5 hours to obtain aluminum silicate modified fibers.
[0043] A method for preparing a long-life large-scale prefabricated block for a dry quenching coke oven comprises the following steps:
[0044] S1, mixing the raw materials of the first block, adding yttrium oxide accounting for 0.8wt% of the total weight of the raw materials of the first block, then putting them into a ball mill, adding water accounting for 22wt% of the total weight of the raw materials of the first block, and wet grinding for 3h. After wet grinding, drying at 120°C for 1.5h, granulating, the granulating pressure is 8MPa, and then molding, the molding pressure is 25MPa, to obtain a first molded block, the protrusion is located on the first molded block;
[0045] The wet-milled Al 2 O 3 The particle size of SiC and mullite is 150-200 mesh, the aspect ratio of the aluminum silicate modified fiber is 12, and the fiber diameter of the aluminum silicate modified fiber is 10-20 μm;
[0046] S2, mixing half of the mass of kaolin, half of the mass of diatomaceous earth and one third of the mass of heat-resistant steel fiber in the second block raw material to form a first mixture, placing the first mixture in a ball mill, adding water accounting for 12wt% of the total weight of the raw materials of the second block, wet grinding for 1.5h, then freeze-drying for 13min, and then heating to 165°C for granulation at a granulation pressure of 9MPa to obtain first particles; in S2, the freeze-drying temperature is -30°C;
[0047] S3, the remaining half of the mass of kaolin, the remaining half of the mass of diatomaceous earth, and the remaining two-thirds of the mass of heat-resistant steel fiber and silicate cement in the raw material of the second block are mixed to form a second mixture, and then the second mixture is put into a ball mill, and water accounting for 12wt% of the total weight of the raw materials of the second block is added, and wet grinding is performed for 1.5h, and then dried at 95°C for 1.5h, and then granulated at a granulation pressure of 5MPa to obtain second particles; the first particles are laid on the lower layer, and the second particles are laid on the upper layer of the first particles, and then formed at a molding pressure of 30MPa to obtain a second molded block, and the groove is located on the second particle laying layer; the particle size of the wet-ground kaolin, silicate cement and diatomaceous earth is 100-200 mesh, and the diameter of the heat-resistant steel fiber is 2-10μm and the length is 3-6mm;
[0048] S4, placing the second molding block into a high temperature furnace for sintering at a sintering temperature of 1700° C. After sintering for 1.5 hours, splicing the first molding block with the second molding block, and then continuing to sinter for 2.5 hours to obtain a prefabricated block.
[0049] Example 2: This example is different from Example 1 in that the raw material components are different. The mass ratio of the first block to the second block is 1:1. The raw materials of the first block include: 25 parts of Al 2 O 3 , 25 parts of SiC, 15 parts of mullite, and 5 parts of aluminum silicate modified fiber; the raw materials of the second block include: 20 parts of kaolin, 15 parts of silicate cement, 10 parts of diatomaceous earth, and 3 parts of heat-resistant steel fiber.
[0050] Example 3: This example is different from Example 1 in that the raw material components are different. The mass ratio of the first block to the second block is 1:1.5. The raw materials of the first block include: 40 parts of Al 2 O 3 , 18 parts of SiC, 10 parts of mullite, and 7 parts of aluminum silicate modified fiber; the raw materials of the second block include: 30 parts of kaolin, 10 parts of silicate cement, 15 parts of diatomaceous earth, and 5 parts of heat-resistant steel fiber.
[0051] Example 4: The difference between this example and Example 1 is that the preparation parameters of the first block are different. In S1, the raw materials of the first block are mixed, and yttrium oxide accounting for 0.5wt% of the raw materials of the first block is added, and then put into a ball mill, and water accounting for 20wt% of the raw materials of the first block is added, and wet grinding is carried out for 2h. After wet grinding, it is dried at 150°C for 1h, and then granulated with a granulation pressure of 10MPa, and then molded with a molding pressure of 20MPa to obtain a first molded block.
[0052] Example 5: The difference between this example and Example 1 is that the preparation parameters of the first block are different. In S1, the raw materials of the first block are mixed, and yttrium oxide accounting for 1wt% of the raw materials of the first block is added, and then put into a ball mill, and water accounting for 25wt% of the raw materials of the first block is added, and wet grinding is carried out for 4h. After wet grinding, it is dried at 100°C for 2h, and then granulated with a granulation pressure of 5MPa, and then molded with a molding pressure of 30MPa to obtain a first molded block.
[0053] Example 6: The difference between this example and Example 1 is that in S2, half the mass of kaolin, half the mass of diatomaceous earth and one third the mass of heat-resistant steel fiber in the second block raw material are mixed to form a first mixture, the first mixture is put into a ball mill, and water accounting for 13wt% of the total weight of the raw materials of the second block is added, wet-milled for 2h, then freeze-dried for 10min, and then heated to 160°C for granulation with a granulation pressure of 8MPa to obtain first particles.
[0054] Example 7: The difference between this example and Example 1 is that in S2, half the mass of kaolin, half the mass of diatomaceous earth and one third the mass of heat-resistant steel fiber in the second block raw material are mixed to form a first mixture, the first mixture is put into a ball mill, and water accounting for 10wt% of the total weight of the raw materials of the second block is added, wet grinding is carried out for 1h, and then freeze-dried for 15min, and then heated to 170°C for granulation. The granulation pressure is 10MPa to obtain first particles.
[0055] Example 8: The difference between this example and Example 1 is that in S3, the remaining half of the mass of kaolin, the remaining half of the mass of diatomaceous earth and the remaining two-thirds of the mass of heat-resistant steel fiber and silicate cement in the raw materials of the second block are mixed to form a second mixture, and then the second mixture is put into a ball mill, and water accounting for 13wt% of the total weight of the raw materials of the second block is added, and wet grinding is carried out for 1 hour, and then dried at 90°C for 1 hour, and then granulated at a granulation pressure of 4MPa to obtain second particles; the first particles are laid on the lower layer, and the second particles are laid on the upper layer of the first particles, and then molded at a molding pressure of 35MPa to obtain a second molded block, and the groove is located on the second particle laying layer.
[0056] Example 9: The difference between this example and Example 1 is that in S3, the remaining half of the mass of kaolin, the remaining half of the mass of diatomaceous earth and the remaining two-thirds of the mass of heat-resistant steel fiber and silicate cement in the raw materials of the second block are mixed to form a second mixture, and then the second mixture is put into a ball mill, and water accounting for 10wt% of the total weight of the raw materials of the second block is added, and wet grinding is carried out for 2h, and then dried at 100°C for 2h, and then granulated at a granulation pressure of 6MPa to obtain second particles; the first particles are laid on the lower layer, and the second particles are laid on the upper layer of the first particles, and then molded at a molding pressure of 25MPa to obtain a second molded block, and the groove is located on the second particle laying layer.
[0057] Example 10: The difference between this example and Example 1 is that in S4, the second molding block is placed in a high-temperature furnace for sintering at a sintering temperature of 1800°C. After sintering for 1 hour, the first molding block and the second molding block are spliced, and then sintered for another 2 hours to obtain a prefabricated block.
[0058] Example 11: The difference between this example and Example 1 is that in S4, the second molding block is placed in a high-temperature furnace for sintering at a sintering temperature of 1600°C. After sintering for 2 hours, the first molding block and the second molding block are spliced, and then sintered for another 3 hours to obtain a prefabricated block.
[0059] Example 12: This example is different from Example 1 in that, in S2, the freeze-drying temperature is -20°C.
[0060] Example 13: This example is different from Example 1 in that, in S2, the freeze-drying temperature is -40°C.
[0061] Example 14: This example is different from Example 1 in that the preparation parameters of the aluminum silicate modified fiber are different.
[0062] S1-1, taking nano aluminum titanate, adding the nano aluminum titanate into an acetone solvent, and dispersing the nano aluminum titanate by ultrasonic method, wherein the ultrasonic frequency of the ultrasonic dispersion is 60 kHz and the ultrasonic time is 5 min, to form a first mixed solution with a mass fraction of nano aluminum titanate of 20%;
[0063] S1-2, mixing the first mixed solution with aluminum silicate fiber at a ratio of 10 ml:5 g at 40° C., with a stirring speed of 200 rpm and a stirring time of 20 min to obtain a second mixed solution;
[0064] S1-3. Then, the second mixed liquid is subjected to a heating evaporation treatment. The heating evaporation treatment is as follows: standing at 120° C. until the liquid in the second mixed liquid is completely evaporated, and then standing at 160° C. for 1 hour to obtain aluminum silicate modified fibers.
[0065] Example 15: This example is different from Example 1 in that the preparation parameters of the aluminum silicate modified fiber are different.
[0066] S1-1, taking nano aluminum titanate, adding the nano aluminum titanate into an acetone solvent, and dispersing the nano aluminum titanate by ultrasonic method, wherein the ultrasonic frequency of the ultrasonic dispersion is 70 kHz and the ultrasonic time is 8 min, to form a first mixed solution with a mass fraction of nano aluminum titanate of 15%;
[0067] S1-2, mixing the first mixed solution with aluminum silicate fiber at a ratio of 10 ml:2 g at 80° C., with a stirring speed of 500 rpm and a stirring time of 30 min to obtain a second mixed solution;
[0068] S1-3. Then, the second mixed liquid is subjected to a heating evaporation treatment. The heating evaporation treatment is as follows: standing at 150° C. until the liquid in the second mixed liquid is completely evaporated, and then standing at 200° C. for 2 hours to obtain aluminum silicate modified fibers.
[0069] Embodiment 16: This embodiment differs from Embodiment 1 in that the side surface of the protrusion is at an angle of 20° to the plane where the first block is located.
[0070] Embodiment 17: This embodiment differs from Embodiment 1 in that the side surface of the protrusion is at an angle of 45° to the plane where the first block is located.
[0071] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.
[0072] The prefabricated blocks obtained in Examples 1 to 17 were treated for 1000 hours at a temperature of 1300° C., a pressure of 0.5 MPa, an atmosphere of 60% nitrogen + 40% oxygen, and an atmosphere wind speed of 1 L / s to obtain a wear rate (the ratio of the wear amount to the mass of the prefabricated block);
[0073] The compressive strength, thermal shock resistance and erosion index were tested at 1100°C and the data were recorded.
[0074] The wear rate and compressive strength can better reflect the service life of the prefabricated block; when the wear rate is small and the compressive strength remains within a certain range, it means that the prefabricated block has a good service life.
[0075] Experimental Example: 1. The above tests were performed on the prefabricated blocks obtained in Examples 1 to 17, and the test results are as follows:
[0076] 1. Explore the effects of different raw material components on the performance of prefabricated blocks;
[0077] Comparative Example 1: Mullite is used as a raw material, and the shape of the prefabricated block is according to Example 1, and the preparation method is according to S1 in Example 1, to obtain the prefabricated block of Comparative Example 1;
[0078] Comparative Example 2: The raw materials of the first block and the second block in Example 1 are directly mixed, and fired according to the molding and firing method of the first block to obtain a whole brick, that is, the prefabricated block of Comparative Example 2;
[0079] Comparative Example 3: The difference from Example 1 is that the aluminum silicate modified fiber in the first block is replaced with aluminum silicate fiber;
[0080] Comparative Example 4: The difference from Example 1 is that the molding method of the second block is the same as that of the first block, that is, the raw material of the second block is processed according to S1, the operation process of S2 and S3 is deleted, and then the prefabricated block of Comparative Example 4 is obtained by firing S4;
[0081] Comparative Example 5: The difference from Example 1 is that in S4, the sintering time of the first block and the second block is set to 2.5 h;
[0082] Comparative Example 6: The difference from Example 1 is that the mass ratio of the first block to the second block is 1:1;
[0083] Comparative Example 7: Al after wet grinding 2 O 3 The particle size of SiC and mullite is 100-110 mesh; the particle size of kaolin, silicate cement and diatomaceous earth after wet grinding is 50-80 mesh.
[0084] Example 1 and Comparative Examples 1 to 7 were compared, as shown in Table 1;
[0085] Table 1 Experimental results of precast block performance under different treatments
[0086]
[0087]
[0088] As can be seen from Table 1, by comparing Example 1 with Comparative Example 1, it can be seen that the prefabricated block obtained by the method in Example 1 has better performances. This may be because, in Comparative Example 1, mullite as a raw material may have defects such as easy oxidation, resulting in poor performance and difficulty in coping with the application of wind and pressure, leading to greater wear, and mullite as a raw material alone has limited compressive strength, etc. The raw material composition in Example 1 can improve the compressive strength and thermal shock resistance of the prefabricated block.
[0089] Comparing Example 1 with Example 2, it can be seen that compared with Example 2 in which the raw materials of the first block and the second block are directly mixed to obtain a whole brick, it is found through experiments that the various performances of the bricks of Example 2 are reduced. This may be because, relying solely on the raw materials of Example 1, the superior performance of each material cannot be fully exerted, which leads to poor performance of the obtained bricks. Because in the process of heat radiation and pressure application, the force exerted on a whole brick will be concentrated inside the material, while the differentiated setting of Example 1 can not only exert the performance of the material according to the effect of heat conduction, but also have the effect of residual diffusion inside it, thereby improving its performance and lifespan.
[0090] By comparing Example 1 with Comparative Example 3, it can be found that compared with Comparative Example 3 in which the aluminum silicate fiber is not modified, Example 1 provides a solution for improving the nanoparticles, which has a more direct effect on improving the performance of the prefabricated block. The reason is that aluminum titanate has a unique crystal structure and excellent thermal stability. Combining aluminum titanate particles with aluminum silicate fibers can enhance the thermal stability and mechanical properties of the fibers, thereby improving the performance of the prefabricated block.
[0091] By comparing Example 1 with Comparative Example 4, it can be seen that in Example 1, adopting different molding preparation methods for the first block and the second block has a good effect. In Comparative Example 4, a unified condition setting is adopted to process different raw materials. Although the performance of the obtained prefabricated blocks is good overall, compared with Example 1, all performances are insufficient. This may be because the raw materials of the first block and the second block are different, and the settings of S2 and S3 help the material to absorb heat layer by layer, thereby reducing its overall loss.
[0092] By comparing Example 1 with Comparative Example 5, it can be seen that the sintering time in Example 1 is more preferred. This may be because the raw materials and molding parameters of the first block and the second block are different. If the sintering time of Comparative Example 5 is used, the second block may not be sintered completely, and its performance is not optimal. Therefore, the method of Example 1 is better.
[0093] By comparing Example 1 with Comparative Example 6, it can be found that the quality of the first block and the second block in Example 1 is more preferred; by comparing Example 1 with Comparative Example 7, it can be found that the particle size of the raw materials in Example 1 is more preferred. This may be because the particle size in Example 1 is suitable for the direct combination of various materials, thereby making the performance better.
[0094] 2. Explore the effects of different preparation parameters on the performance of prefabricated blocks;
[0095] Examples 1-15 were compared, as shown in Table 2;
[0096] Table 2 Test results of different preparation parameters on the performance of prefabricated blocks
[0097] parameter Thermal shock resistance (times) Wear rate % Example 1 50 0.05 Example 2 48 0.07 Example 3 47 0.06 Example 6 46 0.08 Example 7 47 0.10 Example 8 48 0.06 Example 9 46 0.08 Example 12 47 0.07 Embodiment 13 47 0.07 Embodiment 14 48 0.05 Embodiment 15 49 0.06
[0098] As can be seen from Table 2, by comparing Example 1, Example 2 and Example 3, it can be found that the components of Example 1 are more preferred, which may be because the combination of components in Example 1 can increase the strength and anti-loss properties of the obtained prefabricated block. By comparing Example 1, Example 6 and Example 7, Example 8 and Example 9, it can be found that the parameter setting of Example 1 is more preferred for the molding preparation process of the second block. By comparing Example 1, Example 12 and Example 13, it can be found that the freeze-drying temperature of Example 1 is more suitable, which may be because the freezing temperature of Example 1 has a good effect on the raw material microstructure of the first block. By comparing Example 1, Example 14 and Example 15, it can be found that the preparation parameters of aluminum silicate modified fibers have a certain influence on the performance of the prefabricated block, and the parameters in Example 1 are more preferred.
Claims
1. A long-life large prefabricated block for dry quenching coke oven, characterized in that: The prefabricated block comprises a first block and a second block which are spliced to each other, the first block faces the inside of the coke oven, and the second block faces the outside of the coke oven; the mass ratio of the first block to the second block is 1:1-1.5, the first block is provided with a convex block, and the second block is provided with a groove matching the convex block; In terms of weight, the raw materials of the first block include: 25 to 40 parts of Al2O3, 18 to 25 parts of SiC, 10 to 15 parts of mullite, and 5 to 7 parts of aluminum silicate modified fibers; the raw materials of the second block include: 20 to 30 parts of kaolin, 10 to 15 parts of silicate cement, 10 to 15 parts of diatomaceous earth, and 3 to 5 parts of heat-resistant steel fibers.
2. The method for preparing a long-life large-scale prefabricated block for a dry quenching coke oven according to claim 1, characterized in that: The following steps are involved: S1, mixing the raw materials of the first block, adding yttrium oxide accounting for 0.5-1wt% of the total weight of the raw materials of the first block, then putting them into a ball mill, adding water accounting for 20-25wt% of the total weight of the raw materials of the first block, and wet grinding for 2-4h. After wet grinding, drying at 100-150° C. for 1-2h, granulating at a granulating pressure of 5-10MPa, and then molding at a molding pressure of 20-30MPa to obtain a first molded block; S2, mixing half of the mass of kaolin, half of the mass of diatomaceous earth and one third of the mass of heat-resistant steel fiber in the second block raw material to form a first mixture, placing the first mixture in a ball mill, adding 10-13wt% of water accounting for the total weight of the raw materials of the second block, wet grinding for 1-2h, then freeze-drying for 10-15min, and then heating to 160-170°C for granulation at a granulation pressure of 8-10MPa to obtain first particles; S3, mixing the remaining half of the mass of kaolin, the remaining half of the mass of diatomaceous earth, and the remaining two-thirds of the mass of heat-resistant steel fiber and silicate cement in the raw materials of the second block to form a second mixture, then putting the second mixture into a ball mill, adding water accounting for 10-13wt% of the total weight of the raw materials of the second block, wet grinding for 1-2h, and then drying at 90-100°C for 1-2h, and then granulating at a granulation pressure of 4-6MPa to obtain second particles; laying the first particles on the lower layer and laying the second particles on the upper layer of the first particles, and then molding at a molding pressure of 25-35MPa to obtain a second molded block, wherein the groove is located on the second particle laying layer; S4, placing the second molding block into a high temperature furnace for sintering at a sintering temperature of 1600-1800° C., after sintering for 1-2 hours, splicing the first molding block with the second molding block, and then continuing to sinter for 2-3 hours to obtain a prefabricated block.
3. The method for preparing a long-life large-scale prefabricated block for a dry quenching coke oven according to claim 2, characterized in that: The particle size of the wet-ground Al2O3, SiC and mullite is 150-200 meshes, the aspect ratio of the aluminum silicate modified fiber is 10-15, and the fiber diameter of the aluminum silicate modified fiber is 10-20 μm.
4. The method for preparing a long-life large-scale prefabricated block for a dry quenching coke oven according to claim 2, characterized in that: In S2 and S3, the particle size of the wet-ground kaolin, silicate cement and diatomaceous earth is 100-200 meshes, and the diameter of the heat-resistant steel fiber is 2-10 μm and the length is 3-6 mm.
5. The method for preparing a long-life large-scale prefabricated block for a dry quenching coke oven according to claim 2, characterized in that: In S2, the freeze-drying temperature is -40 to -20°C.
6. The method for preparing a long-life large-scale prefabricated block for a dry quenching coke oven according to claim 2, characterized in that: The included angle between the side surface of the protrusion and the upper surface of the first block is 20-45 degrees.
7. The method for preparing a long-life large-scale prefabricated block for a dry quenching coke oven according to claim 2, characterized in that: The aluminum silicate modified fiber is obtained by subjecting the aluminum silicate fiber to nano-enhancement modification with nano-aluminum titanate.
8. The method for preparing a long-life large-scale prefabricated block for a dry quenching coke oven according to claim 7, characterized in that: The preparation method of the aluminum silicate modified fiber comprises: S1-1, adding nano-aluminum titanate into acetone solvent, and dispersing by ultrasonication to form a first mixed solution with a mass fraction of nano-aluminum titanate of 15-20%; S1-2, mixing the first mixed solution with aluminum silicate fiber at a ratio of 10 ml: 2-5 g at 40-80° C. to obtain a second mixed solution; S1-3. Then, the second mixed liquid is subjected to a heating evaporation treatment. The heating evaporation treatment is as follows: standing at 120-150°C until the liquid in the second mixed liquid is completely evaporated, and then standing at 160-200°C for 1-2 hours to obtain aluminum silicate modified fibers.
9. A method for preparing a long-life large-scale prefabricated block for a dry quenching coke oven according to claim 8, characterized in that: The ultrasonic frequency of the ultrasonic dispersion is 60-70 kHz, the ultrasonic time is 5-8 min, the stirring speed of the mixed stirring is 200-500 rpm, and the stirring time is 20-30 min.
Citation Information
Patent Citations
Thermal shock resistance refractory brick and preparation method thereof
CN106542834A
Prefabricated brick prepared from castables and applied to supporting part of oblique air flue in dry quenching structure, and manufacturing method thereof
CN108658610A
Corundum mullite multiphase gradient material for heat recovery coke oven door
CN111153708A
Light wear-resistant heat-insulating composite brick for rotary kiln and preparation method of light wear-resistant heat-insulating composite brick
CN117570715A
Novel concrete pump truck conveying pipeline
CN203718172U